Vegetation of the Continental Northwest Territories at 6 ka BP - MacDonald, Glen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTPollen records are used to reconstruct vegetation in the continental Northwest Territories at 6 ka (6000 14C yr BP). Picea glauca, P mariana, Larix laricina, Populus tremuloides, P. balsamifera, Alnus crispa and A. incana were present throughout their modern ranges in the Boreal and Subarctic Forest Zones by 6000 BP. Pinus banksiana, however, had not yet reached its present northern limits. Population densities of the dominant trees, Picea glauca and Picea mariana, were close to, or as high as, present. In the Mackenzie Delta region the range limit of Picea glauca was approximately 25 km north of its modern location just prior to 6000 BP. In contrast, the northern limits of the forest in central Canada were similar to present. The tundra vegetation close to the edge of the forest was similar to modern Low Arctic Tundra. Development of extensive Sphagnum peatlands had begun in the forested areas and the adjacent Low Arctic Tundra. Palaeoecological information regarding vegetation at 6000 BP remains lacking for the northeastern half of the study area. Therefore, the nature of the vegetation in much of the area now occupied by Low Arctic and Middle Arctic Tundra remains unknown. Important vegetation changes that occurred following 6 ka include : (1) the advance of Pinus banksiana to its present northern range limits, (2) the retreat of the northern range limits of Picea glauca in the Mackenzie Delta region between 6000 and 3500 BP and (3) the rapid and marked increase in the population density of Picea mariana in the treeline zone of the central Northwest Territories at 5000 BP followed by a decline at 4000 BP.